Introducing the next iteration of our sensor box - Haßler, Björn; Bablok, Bernhard (Open Development & Education, 2024)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10456801 ZenodoArchiveConcept: 10456800 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1064 2129771:FNTQ646H
Keywords: _r:AddedByMyEducationEvidence